Production Of Phb By The Bacterial Isolates Of Various Agroindustrial Sites - POORNIMA S; KASTHURI J (International Journal of Pharma and Bio Sciences, 2015)
With the view to minimize the production cost of PHB ( Poly hydroxybutyric acid ), the present investigation has explored the bacterial isolates with the capability to degrade plant materials rich in carbohydrates of various agroindustrial econiches. Further, the components of the production media, Nitrogen Limited Minimal Synthetic Medium ( NLMSM ) has been substituted with cost effective carbon , N2 and KH2PO4 sources. The strain Acinetobacter CN1 an isolate of cashew nut industrial waste reported with the highest yield of PHB The PHB produced by the same was subjected to IR analysis and the results were interpreted.